Edukasi Perilaku Seks pada Komunitas Remaja untuk Mencegah HIV/AIDS - Nurzuhriyah Safitri; Shera Adya Pramitha; Eva Nafisa Mulyana; Syifa Rahma Fauziah; Koni Khoerunisa; Ghea Rizki Septanurisa; Dede Suhendi (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Adolescents are a group that has a high risk of transmitting HIV/AIDS. Teenagers' associations are not effective in triggering an increase in the spread of HIV/AIDS, so teenagers have a great risk of transmitting HIV/AIDS. Sexually Transmitted Diseases (STDs) are an important factor causing an increase in the transmission of HIV/AIDS. Objective: The purpose of this activity is to increase knowledge, apply healthy living in order to know the dangers of HIV/AIDS to avoid the spread of bacteria and viruses in adolescents by following the rules set by health, so that adolescents are able to avoid risky behavior of HIV/AIDS. Method: Community service activities with the theme of Sexual Behavior Education in Adolescents use educational methods with the target of PMR Children. The procedure for the activity is carried out by distributing power points and then explaining about sex education for HIV/AIDS prevention. After explaining the material, evaluate the knowledge of adolescents about sexual behavior education with a question-answer session. Result: The results and discussion of this community service activity are the enthusiasm of the students in this activity with their enthusiasm and presence in participating in this health counseling activity. This activity aims as a medium in applying knowledge from students to teenagers at SMA Negeri 2 Ciamis. It is important for teenagers to increase their knowledge regarding sex education which causes sexually transmitted diseases such as HIV/AIDS. Conclussion: The conclusion of community service activities regarding Sex Education that was carried out to PMR Members of SMA Negeri 2 Ciamis could increase knowledge about sexually transmitted diseases, sex education to prevent HIV/AIDS this event took place smoothly without any obstacles.